2011
DOI: 10.1097/ncc.0b013e3182025020
|View full text |Cite
|
Sign up to set email alerts
|

An Avalanche of Ignoring-A Qualitative Study of Health Care Avoidance in Women With Malignant Breast Cancer Wounds

Abstract: In a preventive perspective, it seems advantageous to bring into focus the health of primary and bereaved caregivers, thereby potentially reducing patient delay and ultimately improving survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 30 publications
0
34
0
1
Order By: Relevance
“…They may delay seeking help and try to hide the reality of the cancer, which highlights the huge impact and shame associated with such a wound on an intimate part of the body, which is deeply significant for sexuality and feminitiy (Boon, et al, 2000). Those with malignant fungating wounds experience may problems such as excessive exudate and leakage, unpleasant odour from the wound, and the fear of being diagnosed with cancer, which may lead to delay in seeing medical help (Lund-Nielsen, et al, 2011).…”
mentioning
confidence: 99%
“…They may delay seeking help and try to hide the reality of the cancer, which highlights the huge impact and shame associated with such a wound on an intimate part of the body, which is deeply significant for sexuality and feminitiy (Boon, et al, 2000). Those with malignant fungating wounds experience may problems such as excessive exudate and leakage, unpleasant odour from the wound, and the fear of being diagnosed with cancer, which may lead to delay in seeing medical help (Lund-Nielsen, et al, 2011).…”
mentioning
confidence: 99%
“…[5][6][7] Even individuals with major health problems 4,8,9 or who are experiencing symptoms [10][11][12] avoid seeking medical care. For example, in one study, 17% of patients diagnosed with rectal tumors reported that they waited a year or more to seek medical consultation after noticing symptoms, with some waiting up to five years.…”
Section: Introductionmentioning
confidence: 99%
“…12 Avoiding medical care may result in late detection of disease, reduced survival, and potentially preventable human suffering. 1,8,13,14 In the present study, we sought to understand why people avoid seeking medical care. Avoidance of medical care has been defined as "keeping away from something [in a medical context] that is thought to cause mental or physical distress."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be noted that a reduction in wound odor had positive patient outcomes, including reduction in social isolation, increase in appetite, and improved body image. 9,[34][35][36] The results of this review demonstrate that CAM products may have the potential to be used as an alternative or complimentary topical therapy to manage odor from MFWs. For instance, if manufactured odor-adsorbing or odor-controlling advanced wound dressings or pharmaceutical agents are not available, the use of CAM like unused green tea teabags in the dressing of an MFW provides a culturally acceptable, cost-effective option for containment of wound odor.…”
Section: Discussionmentioning
confidence: 99%